A CRITICAL RELATIONSHIP BETWEEN WOMEN EMPOWERMENT AND GENDER DISCRIMINATION: A STRATEGIC PERSPECTIVE TO UNDERSTAND THE SUSTAINABILITY OF WOMEN’S LIVES - Biswas, Dr. Prarthita; Roy, Plabani; Chattopadhyay, Adrija (The journal of contemporary issues in business and government, 2022)
Empowerment is a process that is both individual as well as group oriented, since it is through involvement in groups that people most often believe to develop their awareness and the ability to organize and take action to bring about change, often leading to improved decision making capacity at home and at the community level, and greater participation in politics. In the process, empowerment will help women make better use of their talents to lead better lives. They do not aim at being superior to men. They respond as equal and cooperate in order to work towards the common goal. It is therefore a process aimed at changing the nature and direction of systematic forces, which marginalize women and other disadvantaged sections in a given context. The process of women’s empowerment should be critically linked to the issue of sustainability of their own livelihoods. If and only if a woman’s livelihood is ensured in a sustainable manner, would she be a willing stakeholder towards her empowerment. Women’s empowerment needs to be both realized as well as assessed are social, political and economic. Women’s empowerment and women’s education faces a number of social, cultural, economic and psychological barriers which has been highlighted through this paper.